2019
DOI: 10.3389/fonc.2019.00474
|View full text |Cite
|
Sign up to set email alerts
|

The MAP3K7-mTOR Axis Promotes the Proliferation and Malignancy of Hepatocellular Carcinoma Cells

Abstract: Targeted therapy is currently limited for patients with hepatocellular carcinoma (HCC) due to the lack of suitable targets. Kinases play pivotal roles in many cellular biological processes, whereas dysregulation of kinases may lead to various diseases, particularly cancer. However, the role of kinases in HCC malignancy remains unclear. In this study, we employed a kinome small interfering RNA (siRNA) library, comprising 710 kinase-related genes, to screen whether any kinases were essential for cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Recent evidence in the literature has indicated that MAP3K7 may also mediate AMPK-AKT-mTOR signaling, as MAP3K7/TAK1 inactivation is associated with AMPK activation and reduced p-mTOR levels in skeletal muscle [ 209 ]. However, MAP3K7 is reported to mediate mTOR signaling independently of AMPK in hepatocellular carcinoma, possibly via p38 activation [ 225 ].…”
Section: Genetic Aberrations In the Pi3k-akt-mtor Pathway In Prostmentioning
confidence: 99%
“…Recent evidence in the literature has indicated that MAP3K7 may also mediate AMPK-AKT-mTOR signaling, as MAP3K7/TAK1 inactivation is associated with AMPK activation and reduced p-mTOR levels in skeletal muscle [ 209 ]. However, MAP3K7 is reported to mediate mTOR signaling independently of AMPK in hepatocellular carcinoma, possibly via p38 activation [ 225 ].…”
Section: Genetic Aberrations In the Pi3k-akt-mtor Pathway In Prostmentioning
confidence: 99%
“…Three-dimensional cell culture was performed as previously described, with minor modi cations. 34 NanoCulture system was used for 3D cell culture (organogenix). First, 100 ul of medium was added to each well.…”
Section: Three-dimensional Culturementioning
confidence: 99%
“…For the wound healing assay, the cells were transfected with siRNA for 48 h in a T25 culture flask. The cells (1.5 × 10 5 /140 µL) were then plated in culture inserts (IBIDI, Inc., Planegg, Germany) for 16 h [22]. Afterward, the inserts were removed to allow cells to migrate for 4 h. The distance covered by moving cells from time 0 to 4 h was counted as migration distance.…”
Section: Analysis Of Cell Viability Migration and Invasionmentioning
confidence: 99%